P247 Sex-related differences in clinical diagnosis of inflammatory bowel disease. (15th January 2020) - Sempere Robles, L; Purificación, B; Cameo, J; Gutiérrez, A; Laveda, R; García, M; Aguas, M; Medina, L; Martinez, A; Jimenez, N; Nos, P; Jover, R; et al.
Abstract: Background: There is a lack of knowledge of the differences between women and men in clinical behaviour at the onset of inflammatory bowel disease (IBD). We hypothesise a potential diagnostic delay in women in IBD. The aims of this study were: (1) to evaluate the differences in diagnostic effort between women and men with IBD and (2) to assess the sex differences in IBD diagnosis and its impact on the gender roles, the quality of life and the emotional sphere. Methods: We performed a prospective multicentre observational study in adults with a new diagnosis of IBD. The diagnostic process of IBD was reconstructed with semistructured interviews and electronic clinical records. Time to diagnostic resolution after the onset of symptoms and misdiagnosis of IBD in the different levels of the healthcare system were analysed. Patient delay was defined as the period from symptom recognition to first medical consultation. An additional interview was conducted to assess differences between women and men in the influence of IBD in gender roles (directed questions), quality of life (IBDQ-32), anxiety and depression (Hospital Anxiety and Depression Scale) and stress (Disease-Related Stress Appreciation Scale). Results: 121 patients were included (44.6% CD, 53.7% UC, 1.7% IBD-U), (43.8% women 56.2% men) (median age 43 years, 29.5–55). Time to diagnostic resolution was higher in women compared with men, 214 days (93–452) vs. 90 days (40–183) p = 0.001. These differences were more evident in CD 326 days (94–627) / 67 days (28–182) p = 0.007, than in CU 174 days (92–350) / 92 days (47–184) p = 0.078. There were no significant sex differences in patient delay. Misdiagnosis of IBD was found to be 71.7% for women and 48.5% for men ( p = 0.010). Data from Table 1 and Table 2 show the sex differences in the 'influence' of IBD in a sample of gender roles evaluated, the quality of life and the emotional sphere. Conclusion: Our results demonstrate that women with IBD show a higher diagnostic delay and misdiagnosis compared with men. This delay is more evident in CD. Moreover, there is a higher impact of IBD diagnosis in women on the gender roles, the quality of life and the emotional sphere.